Diagnostic Stability of Internet Addiction in Obsessive-compulsive Disorder: Data from a Naturalistic One-year Treatment Study. - BIPETA, RAJSHEKHAR; YERRAMILLI, SRINIVASA SRR; KARREDLA, ASHOK REDDY; GOPINATH, SRINATH (Innovations in Clinical Neuroscience)
Whether internet addiction should be categorized as a primary psychiatric disorder or the result of an underlying psychiatric disorder still remains unclear. In addition, the relationship between internet addiction and obsessive-compulsive disorder remains to be explored. We hypothesized that internet addiction is a manifestation of underlying psychopathology, the treatment of which will improve internet addiction. We enrolled 34 control subjects (with or without internet addiction) and compared them to 38 patients with "pure" obsessive-compulsive disorder (with or without internet addiction). Internet addiction and obsessive-compulsive disorder were diagnosed based on Young's Diagnostic Questionnaire and Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), respectively. Age and Internet Addiction Test scores were comparable in both the control (years: 26.87±6.57; scores: 43.65±11.56) and obsessive-compulsive disorder groups (years: 27.00±6.13 years, p=0.69; scores: 43.47±15.21, p=0.76). Eleven patients with obsessive-compulsive disorder (28.95%) were diagnosed with internet addiction as compared to three control subjects (p=0.039). In the obsessive-compulsive disorder group, no difference in the Yale-Brown Obsessive Compulsive Scale (24.07±3.73 non-internet addiction, 23.64±4.65 internet addiction; p=0.76) score was seen between the internet addiction/obsessive-compulsive disorder and non-internet addiction/obsessive-compulsive disorder groups. As expected, the Internet Addiction Test scores were higher in the internet addiction/obsessive-compulsive disorder group (64.09±9.63) than in the non-internet addiction/obsessive-compulsive disorder group (35.07±6.37; p=0.00). All enrolled patients with obsessive-compulsive disorder were subsequently treated for a period of one year. Treatment of obsessive-compulsive disorder improved Yale-Brown Obsessive Compulsive Scale and Internet Addiction Test scores over time. At 12 months, only two of the 11 patients with obsessive-compulsive disorder (18.18%) fulfilled the Young's Diagnostic Questionnaire criteria for internet addiction. In conclusion, treatment of the underlying disorder improved internet addiction.